Market Analysis and Business Development in Financial Services - Nair, Ashwathy (ATLAS SkillTech University, 2025)
During my time at the company, I committed myself fully to various projects, tackling each challenge with enthusiasm and persistence. I take pride in the contributions I made, including the strategies I developed and implemented, all of which were driven by a focus on innovation, client satisfaction, and business growth.
Project Report on Market Analysis and Business Development in Financial Services (2023-2025) Under the Guidance of Prof. Mehrunnisa Ansari
Keywords: Market Analysis; Business; business growth; client satisfaction; innovation